Angustilobine and andranginine type indole alkaloids and an uleine–secovallesamine bisindole alkaloid from Alstonia angustiloba - Kam, T.S.; Ku, W.F.; Tan, S.J.; Low, Y.Y.; Komiyama, K. (Elsevier, 2011)
A total of 20 alkaloids were isolated from the leaf and stem-bark extracts of Alstonia angustiloba, of which two are hitherto unknown. One is an alkaloid of the angustilobine type (angustilobine C), while the other is a bisindole alkaloid angustiphylline, derived from the union of uleine and secovallesamine moieties. The structures of these alkaloids were established using NMR and MS analysis. Angustilobine C showed moderate cytotoxicity towards KB cells.